Acoustic classification of building façades using statistical methods. (15th January 2021) - Jagniatinskis, Aleksandras; Fiks, Boris; Mickaitis, Marius
Abstract: Indoor acoustic comfort under existing outdoor noise generally depends on the sound insulation characteristics of the building façade. The importance of the acoustic classification of dwelling façade among the classification of other building elements was presented in a COST Action report and by developing the ISO/AWI TS 19488 project. Two approaches are used to describe the façades classification in Europe: first (indirect), establishing the requirements by indoor sound level and, second (direct), specifying the lowest permissible value for the façade sound insulation descriptor depending on the outdoor noise level. Since 2003, the estimated pre-completion acoustic measurement results of dwellings have made it possible to collect sufficient representative statistics of the relationship between building façade sound insulation and the environmental noise data. Simultaneous measurements of noise levels inside the dwelling and the outdoor noise levels on the dwelling's façade give the correlation between noise levels outdoors and indoors as a function of the façade sound insulation. Measurement data were collected for the typical outdoor environment in the main Lithuanian agglomerations where noise levels range from 46 dBA to 70 dBA. Sound insulation of building façades was expressed in D 2m, n T, w and ranged from 30 dB to 50 dB in four equal groups. A statistically objective procedure for the acoustic classification of façades was developed using the obtained regressions between the noise levels outside and inside the premises for each of the façade groups.